Mercado verde - Solano-Leiva, Alexandra (Instituto Tecnológico de Costa Rica, 2017)
This research aims to provide public space capable of generating a positive social impact to a community, by improving the quality of its urban space. Through the implementation of a strategically and carefully crafted space program the project plans to trigger conditions and opportunities present in an overlooked district of the capital. Therefore, this work focuses on an urban-architectural design proposal, through the re-generation and efficient planning of public space, by stimulating the implementation of urban services. A design proposal inter-connecting public facilities that contribute to the economic and social development of the district is presented. To present a context-sensitive proposal that corresponds to the requirements, a diagnosis is prepared at different scales such as social and economic scales. Based on the qualitative and quantitative research tools implemented the proposal of a green community market that strengthens and connects the existing facilities in Los Guido. Additionally, a management model that leads to a proper execution of the project is proposed in such a way that it acts as an urban-triggering agent. This model strives for the entrepreneurial spirit within the local context.
articulador urbano Los Guido 9°52`02.0`N84°02`57.4`W
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2017.
Keywords: Arquitectura comercial; Mercados; Diseño arquitectónico; Arquitectura sostenible; Desamparados (San José)